Implementation Of Promotional Activities for Seuhah Snacks at The Seuhah Festival 03 Event - Sri Marini; Sonny Sanjaya; Idham Sakti Wibawa; Dewi Fitriani; Sara Rabasari; Yayan Setiawan (Universitas INABA, 2023)
The culinary world is closely related to tourism. This sector is utilized by businesspeople as activities in all fields return to normal. In accordance with its instinct to meet food needs, its potential needs to be utilized as much as possible. Various culinary events began to be carried out along with the disappearance of social restrictions. The situation analysis in this community partnership program is focused on the introduction of Seuhah snacks and the achievement of business targets from PT Wibawa Karya Abadi in Seuhah Festival Level 03. Business activities must always be followed by the preparation of a solid strategic plan, to achieve sustainable company success. The role of AKPAR NHI Bandung as a partner is to implement promotional activities in the event. A promotional strategy is needed in marketing an event with the implementation of promotional activities. Promotional activities through advertising go well and using social media platforms will be more in touch with the target market. Likewise, personal selling, direct marketing, sales promotion supports the event according to the expected target. In sales promotion activities, the impact on consumer visits and consumption at the Seuhah 03 hawker festival is more significant. In addition, public relations activities through organizing competitions involving many parties are an indicator that the implementation of these promotional activities is effective.